Pemberdayaan Pemuda Tanggap Bencana (PENDAB) dalam Implementasi Panduan Risiko Bencana - Husni Husni; Widya Lestari; Septiyanti Septiyanti (Warta Pengabdian Andalas, 2021)
Bengkulu is one of the vulnerable disasters areas. Flood is one of disaster that often occurs in the Bengkulu city. The big flood that occurred at the end of 2019 which claimed the lives of 29 people and 13 people were missing. The aim was to increase the capacity of youth in disaster risk management. Activities done through socialization, disaster training, simulation and disaster risk mapping. Socialization done to stakeholders, youth and community leaders. Disaster risk training, the first aid training for youth and making of organization of Youth Responding to Disasters (PENDAB) have done using lecture, discussion, question and answer methods and doing simulation Table Top Exercise (TTX) for disaster management in the neighborhood Association (RT). The training was attended by 15 youths and was conducted in an open field for 2 days while still observing health protocols. This activity has received permission from the Bengkulu Province Covid-19 task force. The results of the training showed that there was an increase in the knowledge and skills of youth about disasters, basic life support (BHD) and first rescue (PP) actions. Youth are expected to apply the knowledge and abilities that have been acquired during the training to provide education about disaster to the community.